Vılçıtrın Sancağı’nda Beylik Yapmış Mihaloğlu Akıncıları ve Faaliyetleri - Rahman ŞAHİN (Gazi Akademik Bakış)
Raiders, consisting of light cavalry units, was very effective in the conquest of Rumelia by the Ottoman Empire. With the expansion of the borders of the state, the raiders expanded their activities towards the interior of Europe and spread all over the Balkan geography. Among the families of the raiders who took charge in certain areas, the most famous ones were Malkoçoğulları, Mihaloğulları, Evrenosoğulları and Turahanoğulları. Raiders took part not only in the conquest of a region but also in the administration. In this context, the raiders who served in many sanjaks in the Rumelia became the representatives of the state. It is known that some of the raider lords served as the governor-general and vizier as well as the district governor. In this study, the Nişan and Tahvil Registers, Ruus Registers, Kâmil Kepeci Registers and Mühimme Registers in the Ottoman Archives were closely examined. In line with the information obtained from archival documents Mihaloğlu raider lords who served as the district governors in Sanjak of Vučitrn in the central Balkans, their kinship ties and their services were mentioned.